Frequency of common types of congenital heart diseases in infants of diabetic mothers - Muhammad Tayyab; Zeeshan Afzal; Wajiha Rizwan (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: Infants born to diabetic mothers are at a heightened risk of having congenital malformations. Congenital heart defects are one of the major health problems in such patients. This study was conducted to assess the frequency of common types of congenital heart diseases (CHD) in infants of diabetic mothers (IDM). METHODOLOGY: It was a cross-sectional, descriptive study conducted at Children’s Hospital Lahore from 10th June 2022 to 9th December 2022. Through consecutive sampling, 160 IDM with CHD were included in the study. The CHD was diagnosed through echocardiography. Diagnostic tests, including pulse oximetry, chest X-rays, and electrocardiography (ECG), were carried out when necessary. Experienced consultant pediatric cardiologists conducted the echocardiography with the help of 2D color Doppler in M mode. RESULTS: The frequency of common CHD in infants born to diabetic mothers was as follows: Patent ductus arteriosus (PDA) in 43 (26.87%), Ventricular septal defect (VSD) in 34 (21.25%), Hypertrophic cardiomyopathy in 28 (17.50%), Patent foramen ovale (PFO) in 20 (12.50%), Atrial septal defect (ASD) in 18 (11.25%), and Transposition of great arteries (TGA) in 17 (10.63%) cases. There is a significant difference in hypertrophic cardiomyopathy in different gestational ages, and a higher rate is seen in gestational age 40-42 weeks (p=0.018). CONCLUSION: In our study, PDA and VSD were the most frequent CHDs in IDM, followed by hypertrophic cardiomyopathy. These findings emphasize the need for early detection and screening in this high-risk group.